5(5x+2x)=9(x-3)

Simple and best practice solution for 5(5x+2x)=9(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(5x+2x)=9(x-3) equation:


Simplifying
5(5x + 2x) = 9(x + -3)

Combine like terms: 5x + 2x = 7x
5(7x) = 9(x + -3)

Remove parenthesis around (7x)
5 * 7x = 9(x + -3)

Multiply 5 * 7
35x = 9(x + -3)

Reorder the terms:
35x = 9(-3 + x)
35x = (-3 * 9 + x * 9)
35x = (-27 + 9x)

Solving
35x = -27 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
35x + -9x = -27 + 9x + -9x

Combine like terms: 35x + -9x = 26x
26x = -27 + 9x + -9x

Combine like terms: 9x + -9x = 0
26x = -27 + 0
26x = -27

Divide each side by '26'.
x = -1.038461538

Simplifying
x = -1.038461538

See similar equations:

| 3x+16=4x+9 | | log(x)=.68 | | 2.68+2.04=-1.02d+6.1 | | -6(v+4)+2v+6=6v+6 | | 4x-11=8x+5 | | 3x-4x+3=32 | | 1.5x+1.5=3 | | 3x+16=91 | | 5x-9-3x=3x-6 | | 4.9x^2+1.85x+55.3=0 | | 10x^2+14x=-x^2+3x+5 | | 30+.5x=21+.65x | | x-7=3(x+5) | | 4x+3=-4+2x+11 | | 2x-8-2x=-1+x | | 2(4y+3)=6 | | 9x-95=38+2x | | 2x+67=6x+7 | | .40x+.60y=24 | | 3yd=12y | | 7(2x-2)=-126 | | 5x+10+7x+50=180 | | -31+2x=-5(4x-7) | | 2x-5y=14fory | | 5x+10+7x+50= | | 9x-4=2r+3 | | 7x(5x+10)=x | | 8-7x-2=-15+4x-12 | | 7x+3=10x-45 | | -5t+7=11t+-25 | | 3x-5=-5-2x | | -8x+5=23 |

Equations solver categories